(untitled) (Fiep Bulletin - online, 2015)
This study aimed to analyze the jump shoot coordination in children basketball’s players. Eight children (10,0 ± 0,5 years; 2,25 ± 0,79 years of practice) were filmed (2D, 100Hz, sagittal plane) shooting to the basket. A biomechanical model was used to analyze angular displacement and velocity of the shoulder, elbow and wrist joints. Children used an “in-phase” movement across the joints (shoulder, elbow and wrist) to increase ball impulse at release. These strategy may be observed because children did not use a counter-movement around the elbow joint to optimize performance. A great joint angular velocity generation was verified, because children were not able to synchronize the peak velocities with the instant of ball release.